The Influence of Leadership Style and Work Motivation on Employee Performance at the Cirebon City Cooperative, Small and Medium Enterprise Trade and Industry Service - Getar Pidia Romadhon; Muhammad Rulianto; Muhammad Alwi (Indonesian Interdisciplinary Journal of Sharia Economics)
Companies play an important role in producing goods or services to achieve profits, and human resources (HR) have a crucial role in determining the success and development of the company. Employees as the main component in the company, need special attention regarding HR management so that the company's goals are achieved. HR development aims to improve the quality of workers to support good performance. This study focuses on the influence of leadership style and work motivation on employee performance at the Cooperatives, Small and Medium Enterprises, Trade and Industry Service of Cirebon City. Based on theory, the right leadership style and high work motivation can improve employee performance. The study used a quantitative method with a descriptive approach. The results of the regression analysis showed that leadership style and work motivation had a positive and significant effect on employee performance. A leadership style that pays attention to the welfare and communication with subordinates, as well as high work motivation, can improve employee performance at the Service. The results of this study provide an important contribution to the company in creating a conducive and productive work environment.